Essays on ethics and feminism - Lovibond, Sabina (Oxford University Press, 2015)
'Essays on Ethics and Feminism' brings together a selection of Sabina Lovibond's shorter writings from 1989 to 2014. The book as a whole is concerned with fundamental ethical questions, including, but not restricted to, questions of feminist ethics such as the nature of value and the good life; moral requirements and their associated epistemology; character-formation and the ideological critique of the processes by which this is carried out. --Back cover.